THE RESEARCH OF MARKET CONCENTRATION OF FERROALLOYS PRODUCTION BRANCH - Biletska, Iryna (Journal of European Economy, 2005)
This paper determines a level of a market power and competitive structure of the world market of ferroalloys. The firms that are forming «core» of the market are identified and their role in a global competition of ferroalloy manufacturers is determined.